Injuries in female and male elite Korean rowing athletes: an epidemiological study - Kim, H. C.; Park, K. J. (Sportverletzung Sportschaden, 2020)
This study aimed to determine the patterns of injury associated with training activities in elite South Korean rowing athletes training for the Olympic Games. Data were prospectively collected between 2010 and 2019 at the Korea National Training Center in South Korea. Three sports medicine doctors assessed athletes, and the data were stratified according to sex, rowing style, weight class, site of injury, and severity of injury. The groups were compared using the c 2 test. The 95 % confidence interval with Poisson rates and exact Poisson test were used for comparison of rates. In total 514 injuries were recorded during the study period, with an average of 2.86 injuries per athlete annually; among these, over half (57.8 %) were mild injuries. Most injuries occurred in the lower extremities (42.0 %), followed by the trunk (30.2 %), the upper extremities (24.9 %), and the head and neck area (2.9 %). Weight class was significantly associated with severity of injury in all rowing athletes (p < 0.001), for both male and female rowing athletes (p = 0.006 and p = 0.014, respectively). Lightweight male athletes demonstrated higher incidence rate of injury than open-weight male athletes (p < 0.001). On the contrary, lightweight female athletes demonstrated lower incidence rates of injury than open-weight female athletes (p < 0.001). These findings on the incidence of training injuries and patterns based on rowing styles, sexes, and weight classes may elucidate the circumstances leading to injuries in elite Korean rowing athletes. Furthermore, these findings may contribute to the development of programs to enhance athletic performance and reduce the incidence of sports injuries. Zusammenfassung